4.2k views
5 votes
If f(x)=3x+10x and g(x)=4x-2 find (f+g)(x)

A:3x+6x+2
B:17x-2
C:3x+14x-2
D:3x-6x+2

1 Answer

5 votes

Answer:

3x^2+14x-2 if you meant f(x)=3x^2+10x and g(x)=4x-2

and I think C was meant to read 3x^2+14x-2

Please correct me if I have mistranslated. Thank you kindly.

Explanation:

I kind of wonder if you meant f(x)=3x^2+10x and g(x)=4x-2.

(f+g)(x)=f(x)+g(x)

=(3x^2+10x)+(4x-2)

=3x^2+10x+4x-2

=3x^2+(10x+4x)-2 I paired 10x and 4x together because they are like terms

=3x^2+14x-2

User Eridana
by
4.7k points